Abincol® (Lactobacillus plantarum LP01, Lactobacillus lactis subspecies cremoris LLC02, Lactobacillus delbrueckii LDD01), an oral nutraceutical, pragmatic use in patients with chronic intestinal disorders - Bonavina, Luigi; Arini, Andrea; Ficano, Leonardo; Iannuzziello, Donato; Pasquale, Luigi; Aragona, Salvo Emanuele; Ciprandi, Giorgio; on digestive disorders, Italian Study Group (Acta Biomedica Atenei Parmensis, 2019)
Chronic intestinal disorders (CID), including inflammatory bowel disease (IBD), such as ulcerative colitis and Crohn’s disease, irritable bowel syndrome (IBS), and diverticular disease (DD), are diseases that relapse episodes. There is evidence that patients with CID have intestinal dysbiosis, so probiotics may counterbalance the impaired microbiota. Therefore, the current survey evaluated the efficacy and safety of Abincol®, an oral nutraceutical containing a probiotic mixture with Lactobacillus plantarum LP01 (1 billion of living cells), Lactobacillus lactis subspecies cremoris LLC02 (800 millions of living cells), and Lactobacillus delbrueckii LDD01 (200 millions of living cells), in 3,460 outpatients (1,660 males and 1,800 females, mean age 55 years) with chronic intestinal disorders. Patients took 1 stick/daily for 8 weeks. Abincol® significantly diminished the presence and the severity of intestinal symptoms and improved stool form. In conclusion, the current survey suggests that Abincol® may be considered an effective and safe therapeutic option in the management of patients with chronic intestinal disorders.